Islamic Food bank Sebagai Solusi Ketidakamanan Pangan Perspektif Maqashid Syariah Jamaluddin Athiyyah - Maulana, Hartomi; Royyana Akmalia; Sabila, Muna Ahda (DAS Institute, 2025)
Food insecurity caused by poverty is a global issue that requires attention and solutions. In response, food banks, as non-profit organizations coordinating the distribution of surplus food, offer a potential solution to hunger and food insecurity. In practice, food banks have mechanisms and goals similar to Zakat, Infaq, and Sadaqah (ZIS) in Islam. However, in some aspects, food banks have not fully addressed the application of Islamic principles, particularly concerning the halal status of food. Therefore, the concept of an Islamic food bank is needed as an implementation aligned with maqasid shariah principles. Maqasid shariah, which includes the protection of religion, life, intellect, lineage, and wealth, was further developed by Jamaluddin Athiyyah, providing an ethical and legal framework for social activities like food banks. This study aims to identify how food banks can contribute to social welfare through fair and effective food distribution, and how Islamic principles can ensure justice, transparency, and accountability in their management, in line with the maqasid shariah goals according to Jamaluddin Athiyyah's perspective. The analysis evaluates general food bank practices, assesses their alignment with maqasid shariah, and offers recommendations for improving sustainability. This research employs a qualitative approach with a literature review method. The findings show that food banks implemented in accordance with maqasid shariah not only meet food needs but also strengthen social networks, improve the overall quality of life, and provide peace of mind for Muslim communities.